Pembentukan Kelompok Belajar untuk Siswa pada Pembelajaran Daring - Utami, Dewi Sri; Appulembang, Oce Datu (Yayasan Sukma, 2022)
The Covid-19 pandemic has brought changes in human life. The learning process that was originally carried out directly in the classroom, now has to be done at home by utilizing technology and internet networks. Online learning makes communication between students and their friends limited and studentsâ€™ ability to work together is reduced. For this reason, as a teacher, you must be able to design learning methods that can make students still able to have good communication with their friends. The method of forming study groups for students is one of the effective methods used in the midst of online learning as it is today. Therefore, the purpose of writing this paper is to explain the importance of group formation methods in developing student collaboration from a Christian perspective. This paper was prepared using a descriptive qualitative research method. Christian teachers when dividing students into groups, must divide fairly and see students as valuable creations in the likeness and image of God. So that in the learning process in groups, Christian teachers must be able to guide students not only to learn about love but to be able to practice love itself in their groups. The existence of a group formation method is not only useful for developing student collaboration skills, but also allows students to appreciate every difference that exists in their group.Pandemi Covid-19 membawa perubahan dalam hidup manusia. Proses pembelajaran yang semula dilakukan secara langsung di kelas, kini harus dilakukan di rumah masing-masing dengan memanfaatkan teknologi dan jaringan internet. Pembelajaran yang dilakukan secara daring, membuat komunikasi siswa dengan temannya menjadi terbatas dan kemampuan siswa dalam bekerja sama menjadi berkurang. Untuk itu, sebagai guru harus bisa merancang metode pembelajaran yang dapat membuat siswa tetap bisa memiliki komunikasi yang baik dengan teman-temannya. Metode pembentukan kelompok belajar untuk siswa menjadi salah satu metode yang efektif digunakan di tengah pembelajaran daring seperti sekarang ini. Maka dari itu, tujuan penulisan paper ini untuk memaparkan tentang pentingnya metode pembentukan kelompok dalam mengembangkan kerja sama siswa ditinjau dari perspektif Kristen. Paper ini disusun dengan metode penelitian kualitatif deskriptif. Guru Kristen pada saat membagi siswa ke dalam kelompok, harus membagi dengan adil dan melihat siswa sebagai ciptaan berharga yang serupa dan segambar dengan Allah. Sehingga dalam proses pembelajaran di kelompok, guru Kristen harus bisa menuntun siswa untuk tidak hanya belajar tentang kasih tetapi mampu mempraktikkan kasih itu sendiri di dalam kelompoknya. Adanya metode pembentukan kelompok, tidak hanya berguna untuk menembangkan keterampilan kerja sama siswa, tetapi membuat siswa bisa menghargai setiap perbedaan yang ada di dalam kelompoknya.Â